Rediscovering the cardiorenal syndrome: from theory to practice - Huerta-Velázquez, José Miguel; Jimenez-Curiel, Alexa; Santiago-Maciel, Daniel Felipe (International Journal of Research in Medical Sciences, 2022)
Cardiorenal syndrome (CRS) is a state of advanced involvement that occurs between the heart and the kidneys, with both organs being affected by multiple causes, either secondary to a systemic pathology, or the dysfunction of one of these organs causing dysfunction on the other, acutely or chronically. Typically, there are five different types with different pathophysiology, but with the same purpose: cardiac and renal involvement. Epidemiological data from meta-analysis carried out around the world indicate that it is a very common pathology, yet commonly missed by clinicians. In patients with kidney or heart disease, which places them in a position to develop the syndrome, the first contact doctor must actively search for the diagnosis. In hospitalized patients, especially among those with previous cardiac or renal pathology, this syndrome has an important relevance, since its incidence is very high and early diagnosis is extremely important for an adequate treatment and thus avoid the perpetuation of damage to both organs. An early diagnosis can reduce the mortality rate, since it has been estimated that it increases by approximately 15% for every 10 ml / min reduction in GFR.